Influence of the flood pulse on the reproduction of Tocantinsia piresi (Miranda Ribeiro) and Auchenipterus nuchalis (Spix & Agassiz) (Auchenipteridae) of the middle Xingu River, Brazil - FREITAS, Tiago Magalhães da Silva (Universidade Federal do Pará, 2017)
This study investigates the influence of the flood pulse on the reproductive biology of the auchenipterids Tocantisia piresi (Miranda Ribeiro, 1920) and Auchenipterus nuchalis (Spix & Agassiz, 1829) from the middle Xingu River in the Brazilian state of Pará. The specimens were collected every three months between April, 2012, and January, 2014, covering four distinct periods (flood, ebb, dry, and filling). The sex ratio, size at first maturity, gonadosomatic index, and condition factor were analysed in the two species, and evaluated in the context of the different hydrological periods. A total of 897 specimens of T. piresi were collected, of which 467 were female, and 430 males, and 383 A. nuchalis (286 females and 97 males). In T. piresi, the sex ratio was biased only in the filling and ebb periods, whereas in A. nuchalis, it departed significantly from the expected ratio of 1:1 in all periods, with a predominance of females. The female T. piresi mature at a smaller size than the males, with the opposite of the pattern being recorded in A. nuchalis. In T. piresi, the breeding peak was observed during the low water periods, whereas in A. nuchalis, the peak was recorded in the flood periods. Male and female T. piresi presented similar positively allometric growth rates, whereas in A. nuchalis, growth was negatively allometric, but rates were different between genders. A higher condition factor was recorded in the females of both species during the ebb period. Overall, the results of this study reveals distinct flood pulse effects on the reproductive parameters of the two auchenipterid species studied; for A. nuchalis the spawning seems to happen at the flood period and for T. piresi at the dry season of the middle Xingu River.